A review of methodology for the analysis of pyrethrin and pyrethroid residues in food of animal origin. Issue 5 (4th May 2018) - Tuck, Sarah; Furey, Ambrose; Crooks, Steven; Danaher, Martin
ABSTRACT: Pyrethrin and pyrethroid pesticides are commonly used in crop protection and animal health, to control pests. As a result, they can potentially transfer into food if good agricultural practice is not followed or even due to accidental contamination. The analysis of these compounds has been widely reported in crops and the environment. However, the analysis of pyrethrin and pyrethroids has not been reported frequently in foods of animal origin, particularly animal tissues. The focus of this review is to report on pyrethrin and pyrethroid analysis including key aspects such as chemistry, choice of target matrix, sample preparation, chemical analysis, legislation and method validation. This review shows that most methodologies for the analysis of these compounds are based on gas chromatography with the trend in recent years to move towards GC-MS or GC-MS/MS based platforms. This review shows that these compounds can also be satisfactorily analysed by LC-MS/MS, which can be advantageous because of shorter chromatographic run times. A wide range of sample preparation procedures have been applied in analytical methods and more complex protocols are required for GC applications, whereas more crudely prepared extracts can be analysed by LC-MS/MS. This review demonstrates that pyrethrin and pyrethroid residues should be included as analytes in multi-class analytical methods for pesticides and veterinary drug residues in animal derived foods.